Tracking violations in visual resources in the landscape of Asveja regional park - Vaitkevičienė, Jelena; Kumetaitienė, Aušra (Geodesy and Cartography, 2015)
Research on landscape stability of regional parks, the status and conditions of the objects and attributes of natural and cultural heritage serve a significant contribution to the survey of the properties of the national heritage possessed in the preserved areas of the Republic of Lithuania. The objective of this article is the analysis of visual landscape resources of Asveja Regional Park in terms of the current state and conditions, changes and modifications within territorial sites as well as with regard to the accumulation and concentration of the objects, their scope and extent. It is possible to assess the efficiency and expediency of an environmental impact taking into consideration research observations. The area of Asveja Regional Park significant for an intense anthropogenic environmental impact and defined in monitoring data sheets and records of Asveja Regional Park referring to 2005–2010 has been selected. Monitoring has been carried out by the Authority of Asveja Regional Park according to the Lithuanian State Environmental Monitoring Program. In order to solve the conflict between society and the environment, the project preconditioned by the use of natural resources and the preservation of valuable objects has been developed. Study on landscape monitoring has been carried out at the local level. It has been fixed within the selected territories, namely, standardised reference sites chosen on the basis of the geosystem and targeted on geophysical–geochemical sensitivity and technogenization with preference for the analysis of the most vulnerable geopotencial territories, i.e. nature reservations, protected areas, shores and the coastlines of lakes providing a wide range of recreational potential. Natural and cultural heritage objects violating regulations on requirements for landscape preservation have been observed in the determined standardized areas as visual resources of the regional park landscape. In order to determine the territorial dispersion of the infringements of requirements for landscape protection, the authors have performed a spatial distribution analysis of visual observation targets calculating nuclear or kernel density. Weight points of requirements for the items violating landscape protection have been attributed thus considering the monetary value of the prescribed fines (following regulations on the specific type of the caused damage). The analysis of the study on specified spatial distribution has been accomplished involving some groups of objects violating requirements for landscape protection. Within the conducted research, the authors investigated the targets that violated requirements for landscape protection and made use of the recorded data. The available findings derive a conclusion that a major part of infringements are considered as recreation violations (40%); violations in usage, trespassing, visiting forests and woodlands (5%) comprise a minor part. In general, the greatest accumulation of infringements are determined to be located in the western and south-eastern part of Asveja Regional Park where their intensity exceeds more than 6 times the concentration of infringements in other investigated areas and territories.